(untitled) (OODBODHAN, 2026)
This study examines the effect of alumina (Al2O3) nanoparticles addition on a single cylinder, four stroke diesel engine fueled with pine-diesel biodiesel blends. The test fuel studied were a blend of 20% pine oil and 80% diesel (B20) containing 25, 50 and 75 ppm Al2O3 nanoparticles as an additive. The experimental test was conducted at different compression ratios of 15 and 17 in various loading conditions. While the thermochemical properties of the blended fuel were tested at central laboratory of Nepal Oil Corporation using standard methods and the results were found to be comparable to those of commercial diesel. According to performance evaluation, all fuel samples showed an increase in indicated power with increasing engine load. Both diesel and B20 fuel are outperformed by the B20+75 ppm test fuel blend, which produces the maximum indicated power of 4.49 kw at high load. This enhancement is connected to improved fuel atomization and improved combustion that the nanoparticles encouragement in diesel engine. All blends doped with nanoparticles showed a decrease in brake specific fuel consumption (BSFC) with increasing load; the B20+75 ppm fuel blends at CR 17 had the lowest BSFC of 0.30 kg/kWhr at high load, a 10% decrease from CR 15. With the load and compression ratio increase, brake thermal efficiency (BTE) increased up to 23.86% at high load for the B20+75 ppm blend at CR 17, which is about 4.42% more than commercial diesel. All things considered, adding Al2O3 nanoparticles to pine-diesel biodiesel blends greatly enhanced engine performance and combustion characteristics without necessitating any engine modifications. These findings demonstrate the potential of Al2O3 Nano-additives as a practical strategy for raising the effectiveness and fuel economy of compression ignition engines that run on biodiesel.